Muhammadiyah Masa Orde Lama: Kiprah Pergerakan Politik Muhammadiyah Pada Era Pemerintahan Orde Lama Tahun 1945 – 1966 - Mahadika, Alam (At-Turost : Journal of Islamic Studies, 2022)
This paper discusses the gait of the Muhammadiyah political movement in the Old Order era of 1945-1966. The research method used is historical research that examines past events, including heuristics, source criticism, interpretation, and historiography, with data reduction analysis: data, presentation, conclusion, and verification. The findings of Muhammadiyah's political progress during the Old Order period, which mainly played a role in the formulation of the actual state, were the representative of Muhammadiyah, Ki Bagus Hadikusumo, an Islamic Nationalist figure who fought for the establishment of Islamic law in the formulation of the primary state. Ki Bagus Hadikusumo did not want the formation of an Indonesian state as an Islamic state, but a form that contains Islamic law, where leaders have good morals as implied in the Al-Quran and Sunnah. After that, Muhammadiyah also took an active role in the Masyumi political party. Masyumi Muhammadiyah Party gave its political aspirations based on Islam because three things marked Muhammadiyah's activities within Masyumi, firstly the number of Muhammadiyah people in the management of PP Masyumi tended to rise and remain above The previous 50% was below 50% (1945) and below 30% (1949). In the management of Masjumi in 1951, 1952, and 1954, Muhammadyah's contributions were 56%, 54%, 53%, respectively. After that, the contestation for the first general election in Indonesia in 1955, siding with Muhammadiyah, remained in the Masyumi Party, the second winner. The number of votes fell by 114,267 compared to the election for members of the House of Representatives.